Performance Enhancement Using Nano Particles in Modified Passive Solar Still. (2016) - Gupta, Bhupendra; Shankar, Prem; Sharma, Raghvendra; Baredar, Prashant
Abstract: Conventional single basin passive solar still has low productivity. In this context, productivity of passive solar still is increased by using nanoparticles in modified still. Modified still has white painted sidewalls. Nanoparticles enhance thermal characteristics of the fluid by increasing surface area for heat transfer. CuO nanoparticles have been used in modified still to increase productivity and efficiency. Experiments have been performed at water depth of 5 cm and 10 cm with nanoparticles added 0.12% by weight. The performance is compared with the conventional solar still kept at same place (Jabalpur, India, 23° 10' N, 79° 59' E) in same ambient conditions. Modified solar still with added nanoparticles produces 3445 ml/m 2 -day and 3058 ml/m 2 -day at water depth of 5 cm and 10 cm respectively, while conventional solar still yields 2814 ml/m 2 -day and 2351 ml/m 2 -day for respective water depth. In this experimental work, error analysis and cost analysis has also been carried out.